Heavily Doped and Highly Conductive Hierarchical Nanoporous Graphene for Electrochemical Hydrogen Production. (7th September 2018) - Chen, Linghan; Han, Jiuhui; Ito, Yoshikazu; Fujita, Takeshi; Huang, Gang; Hu, Kailong; Hirata, Akihiko; Watanabe, Kentaro; Chen, Mingwei
Abstract: Heavy chemical doping and high electrical conductivity are two key factors for metal‐free graphene electrocatalysts to realize superior catalytic performance toward hydrogen evolution. However, heavy chemical doping usually leads to the reduction of electrical conductivity because the catalytically active dopants give rise to additional electron scattering and hence increased electrical resistance. A hierarchical nanoporous graphene, which is comprised of heavily chemical doped domains and a highly conductive pure graphene substrate, is reported. The hierarchical nanoporous graphene can host a remarkably high concentration of N and S dopants up to 9.0 at % without sacrificing the excellent electrical conductivity of graphene. The combination of heavy chemical doping and high conductivity results in high catalytic activity toward electrochemical hydrogen production. This study has an important implication in developing multi‐functional electrocatalysts by 3D nanoarchitecture design. Abstract : Hierarchisches nanoporöses Graphen mit stark dotierten katalytischen Domänen auf hoch leitfähigen Substraten wurde durch ein zweistufiges Dampfabscheidungsverfahren hergestellt. Die nanoskopische Architektur hebt die wechselseitige Beeinträchtigung von Katalyseaktivität und Leitfähigkeit in chemisch dotiertem Graphen auf und weist einen neuen Weg für die Entwicklung leistungsfähiger multifunktionaler Graphen‐Katalysatoren.